The Behaviour Of LNAPL In Sand Due To Precipitation - Mah, Chia Ling (Universiti Sains Malaysia, 2017)
The number of oil spill cases keeps increasing and turning serious. Any incidents can cause oil spill such as pipeline leakage, transportation accident, natural disasters or exploration of oil tanker. Once the oil spill happened, the remediation work may take long time to clean the contaminated soil completely. The oil spill happened on the ground and the sea. Oil has a density less than water, especially light non-aqueous phase liquid (LNAPL) will float on the sea surface and groundwater table. This will truly bring effect to the environment, animals and humans. Oil covered the sea surface, causing oxygen and sunlight difficult to go into the sea which threaten the aqua life. The pollution of groundwater will lead to health problems when human consumed the polluted groundwater as drinking water. However, before starting the remediation work, the movement of the oil in the ground needs to be determined. Hence, one dimensional (1-D) column tests were carried out to study the rate of migration of the LNAPL due to precipitation because the movement of oil may be affected by rain water percolation. The column test started with drainage for 4 hours, infiltration of diesel for 24 hours, precipitation for 1 hour and percolation of water for 24 hours. This test was conducted to simulate the real case scenario. When precipitation occurred, the droplets infiltrate into the ground and store as groundwater. The LNAPL infiltrate the ground surface and occupied the pore between the soil particles. During precipitation, diesel will migrate downwards together with rain water into the saturated capillary zone. The infiltrated water may occupy the pores by pushing diesel downward and entrapped in deeper soil. The different intensity of precipitation and volume of diesel was used to understand the effect on the saturation of diesel in height.